2018
DOI: 10.1155/2018/7804642
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate and Perceived Experience Differ Markedly for Children in Same- versus Mixed-Gender Soccer Played as Small- and Large-Sided Games

Abstract: This study examines heart rate (HR) and perceived experience during same- versus mixed-gender soccer played as small- (SSG) and large-sided (LSG) games. HR, rating of perceived exertion (RPE), and fun scores were determined in 134 pupils (50 girls, 84 boys) randomly assigned to same- and mixed-genders formats playing 2x15-min of SSG (2v2, 4v4) and LSG (12v12) in a random order (~50 m2/player). HR was lower (p≤0.03) for girls when playing together with boys than when playing alone (71±10 versus 77±7%HRmax), whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 42 publications
(55 reference statements)
0
16
0
Order By: Relevance
“…As well as numerical equality SSGs, the study findings recommend the use of full games, which also cause high levels of intensity during motor performance. The study developed by Póvoas et al [14] followed this tendency, although they found that the HR avg was significantly greater in SSGs than during full games. In contrast to the present study (5 vs. 5 format), these authors referred to the 12 vs. 12 playing format as a full game.…”
Section: Etl and Itl Variables According To The Game Situationmentioning
confidence: 93%
See 2 more Smart Citations
“…As well as numerical equality SSGs, the study findings recommend the use of full games, which also cause high levels of intensity during motor performance. The study developed by Póvoas et al [14] followed this tendency, although they found that the HR avg was significantly greater in SSGs than during full games. In contrast to the present study (5 vs. 5 format), these authors referred to the 12 vs. 12 playing format as a full game.…”
Section: Etl and Itl Variables According To The Game Situationmentioning
confidence: 93%
“…Equally, according to the type of intensity of the physical activity performed in PE classes, the students should spend at least 50% of the time recording MVPA values for adequate cardiovascular work in order to prevent being overweight and obesity [1]. Invasion sports are included in the Spanish study program, and they have great potential to maintain the students' motivation while they perform a very demanding activity [14], providing greater opportunities for reaching MVPA [15]. In this sense, Kalajas-Tilga et al [16] reported that intrinsic motivation of adolescent students toward physical education should be increased to improve MVPA, since there is a relationship between the two.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recommendation was to prevent a rise in blood glucose levels when performing high-intensity exercise. 22,23 Prevention of a rise in glucose levels was necessary as the heart rates of healthy adolescent boys during small-sided football games are around 79% 24 to 84.6% 25 of the maximum heart rate. The participants of the pilot study used heart rate monitors (Polar H10 coupled with Polar A370 watch, Polar) to check whether they exceeded the exercise intensity.…”
Section: Football Programmentioning
confidence: 99%
“…A literature search indicates that gender-related research in PE is most often concerned with girls’ well-being, inclusion, and engagement ( Garrett, 2004 ; Oliver and Lalik, 2004 ; Oliver et al, 2009 ; Hill, 2015a ; Oliver and Kirk, 2016 ; Lamb et al, 2018 ) even if there are studies focused upon boys’ relation to PE ( Davison, 2000 ; Drummond, 2003 ; Tischler and McCaughtry, 2011 , 2014 ; Hill, 2015b ; Gerdin, 2017 ; Gerdin and Larsson, 2018 ; Monney and Gerdin, 2018 ). Benefits of single-sex vs. mixed sex PE has been studied in a few studies concerning, for instance, students’ activity levels or heart rate in single-sex or mixed groups (e.g., Mutz and Burrmann, 2014 ; Póvoas et al, 2018 ; Wallace et al, 2020 ). Also, gender studies concerning experiences of sexual minorities in sports and PE have increased in the last few years (see, e.g., Kavoura and Kokkonen, 2020 ).…”
Section: Introductionmentioning
confidence: 99%